Effects of â€œPedagogical Cyclesâ€ on Studentsâ€™ Learning at Secondary Level - Hussain, Ishtiaq; Sardar, Farzana; Ahmed, Maqsood; Akhtar, Shagufta; Lodhi, Ishrat (Richtmann Publishing, 2011)
The importance of education can not be denied as it plays the vital role in the development of an individual and ultimateprogress of a nation is absolutely depends on the quality of education that is planned for young generation. There are different strategies,methods and techniques which make the teaching learning more effective the rules and guidance provided by pedagogy helps in achievingthe aims, goals and objectives of education. The main objectives of this study were (a) to find out the relative effects of multiple pedagogicalcycles in classroom teaching on studentsâ€™ learning at secondary level. (b) To investigate whether the students can retain the learning for alonger time when taught through pedagogical cycle. The population of the study was the students of secondary level in the schools of KhyberPakhtunkhwa. The study was delimited to the students of 10th class of Urdu medium schools .Only one Section of 10th class ofGovernment Girls High School K.D.A. Kohat was taken as sample of the study. Sample students were further divided into two groups,i.e. experimental and controlled groups on the basis of their pre-test scores. Experimental group was taught by pedagogical cycle while theControl group was taught by traditional method for a period of six weeks. At the end of the treatment, a post-test was administered andscores of pre-test, post-test were served as data of the study. T-test and analysis of variance were applied to know the significance ofdifference between the scores of groups at 0.05 level.